F or V-induced activation of (Co, Ni)2P during electrocatalysis for efficient hydrogen evolution reaction. Issue 40 (1st October 2019) - Liu, Li; Tao, Keyu; Dan, Huamei; Hai, Yang; Gong, Yun
Abstract : A series of (Co, Ni)2 P– x F and post-(Co, Ni)2 P– x F electrocatalysts with different compositions, morphologies and HER performances were synthesized. Among them, post-(Co, Ni)2 P–10F exhibits the best HER activity. Abstract : A series of (Co, Ni)2 P– x F electrocatalysts with different compositions and morphologies were grown on Ni foam (NF) in the absence or presence of different amounts ( x mg) of NH4 F. After electrolysis in the hydrogen evolution reaction (HER) process for 10 h, the electrolyzed samples, post-(Co, Ni)2 P– x F, display different HER electrocatalytic activities. Among them, post-(Co, Ni)2 P–10F exhibits the best activated HER performance with an overpotential ( η 10 ) of 85 mV to reach a 10 mA cm −2 HER current density, which is much better than that of (Co, Ni)2 P–10F ( η 10 = 158 mV) and comparable to that of the commercial Pt/C benchmark ( η 10 = 56 mV). Furthermore, post-(Co, Ni)2 P–10F exhibits good long-term durability in KOH solution. It is associated with its nanoplate arrays constructed from numerous tiny nanoparticles, and the partial transformation of metal–P into metal–O bonds during the electrolysis activation gives more suitable H adsorption free energy (Δ G H ) on the O-site (−0.022 eV) than on the P-site (0.086 eV). In contrast, the free-F sample, post-(Co, Ni)2 P, shows inferior HER behavior in comparison with (Co, Ni)2 P. F-Incorporation plays a role in the activation process of metal phosphides, and the mechanism is explored by density functional theory (DFT) calculation. Furthermore, the V-induced activation effect on the HER performance is also observed for the electrolyzed metal phosphide. The η 10 at post-(Co, Ni)2 P–10F–V is 89 mV, which is much lower than that at the original sample, (Co, Ni)2 P–10F–V (155 mV).